LEGAL PROTECTION OF LURIK ART CONSERVATION THROUGH INTELLECTUAL PROPERTY RIGHTS 2 IN KLATEN REGENCYLEGAL PROTECTION OF LURIK ART CONSERVATION THROUGH INTELLECTUAL PROPERTY RIGHTS 2 IN KLATEN REGENCY - Fitriono, Riska Andi; Sarwono, Sarwono (Faculty of Law, Universitas Sebelas Maret, 2019)
This article aimed to analyze legal protection of Lurik Art Conservation Through Intellectual Property Rights in Klaten Regency. Klaten is the area that is most concerned with the survival of lurik weaving. There is someone mentioned that the Klaten Regency was the capital of lurik weaving. Because the weaving of Looms are not machines or Alat Tenun Bukan Mesin (hereinafter abbreviated to ATBM) is a mainstay of this city. There are countless villages that become centers of lurik craftsmen. This research is empirical or non-doctrinal research, which is a study that sees the law not only from the perspective of legislation, but also sees the law in its implementation. The results of the study show that the first legal protection in preserving the current lurik art in Klaten, namely the Klaten Regency Government, then stipulates the Regent's Regulation Number 53 of 2010 Article 23 Paragraph (9) on the Daily Batik and Traditional Weaving Lurik Service or ATBM Striated and the Klaten Regent's Decree Number : 065/1014/06 December 30, 2010 on Wearing Traditional Weaving, Motives, Colors and Free Models with Attributes. Furthermore, based on the Decree of the Regent of Klaten Number 050/84 of 2016 on Klaten Regency's Superior Products, batik striated is one of the superior products of Klaten Regency. With the issuance of these rules as an effort to protect and preserve lurik art in Klaten district and referring to Law Number 28 of 2014 on Copyright, it has regulated the forms of protection of lurik art in Klaten through Article 40 paragraph (1). The Second Protection of Intellectual Property Rights Against Lurik Art, namely Protection of lurik artworks, besides being accommodated in Law Number 28 of 2014 on Copyright (Copyright Law) and Trademark Law and other intellectual property right laws. Elucidation of Article 40 paragraph (1) letter j of the Copyright Law. The work is protected because it has artistic value, both in relation to the picture, style, and color composition. The Copyright Act also emphasizes that it is important to protect Copyright because every creator, in this case, the creator of the lurik motif has the right to moral rights and economic rights.